FACTORS AFFECTING JOB SATISFACTION - Moh Sutoro (Sekolah Menengah Kejuruan (SMK) Pustek, 2020)
The task of educational institutions is to carry out a quality teaching and learning process, and the key is in the teacher. Therefore, the institution should be ensure the quality of teacher performance is maintained. This study aims to identify several factors that affect teacher performance, but the measure is job satisfaction. This is intended, to find out how the treatment of a teacher to carry out the task as well as possible, which is influenced by mood. To test the validity of the research, quantitative methods and structural equation modeling analysis were used. As for data collection techniques, researchers used a questionnaire, which was given directly to the respondent (teacher). The results showed, 1) Motivation to be a good mediator in influencing job satisfaction. 2) A good work culture can influence work behavior and shape work morale. 3) Low stress levels can affect teacher behavior to work better, because they are in a good mood (satisfied). This means that there are many non-physical factors that significantly affect teacher performance, including work culture, stress, and motivation. Therefore, in the aspect of human resource management, the treatment of institutions should be based on a humanitarian approach